P026: Dominating the vent: A flipped classroom approach to enhance emergency medicine resident ventilator management. (May 2019) - Cortel-LeBlanc, M.; Landreville, J.; Cheung, W.; Pan, A.
Abstract : Innovation Concept : Ventilator management is an essential skill and a training objective for emergency medicine (EM) specialists in Canada. EM trainees obtain the majority of this training during off-service rotations. Previous attempts to strengthen ventilator knowledge include lectures and simulation – both of which are time and resource intensive. Given the unique features of ventilator management in the ED, we developed an ED-specific ventilator curriculum. The purpose of this study is to 1) identify resident needs regarding ventilator curricula and 2) assess resident response to this pilot curriculum.Methods : A needs-assessment survey administered to RCPSC- and CCFP-EM residents at The Ottawa Hospital (TOH) showed the majority of residents (87%, n = 31 respondents) believe there is a need for more ED-focused ventilator management training, and only 13% felt confident in ventilator management. Ten on-line modules were prepared by an EM-Critical Care attending, and distributed on-line to all EM trainees at TOH (n = 52). Mid- and post-implementation surveys are used to assess residents' confidence in ventilator management, and perceived usefulness of the curriculum. User feedback from focus groups constitutes part of the curriculum evaluation.Curriculum, Tool or Material : Employing a flipped classroom approach, ten on-line modules were distributed to RCPSC- and CCFP-EM trainees at TOH. Each module requires less than ten minutes to complete and focuses on a single aspect of ventilation. The modules are available for residents to complete at their own pace and convenience. At curriculum completion, an EM-Critical Care attending physician facilitates an interactive session.Conclusion : Mid-implementation survey results demonstrate increased confidence in independently managing ventilated patients in the ED (13% pre- vs. 56% mid-implementation), and an increased perception of having sufficient ventilator training (26% pre- vs. 78% mid-implementation). All respondents felt the modules were of appropriate length, content was easy to follow, and that the modules should be part of the residency curriculum. Our ED-specific online ventilator modules area a viable tool to increase residents' confidence in ventilator management. This novel curriculum could be adopted by other residency programs and continuing professional development initiatives. Future work will include post-implementation data-gathering, and formal curriculum evaluation.